Weak by the machines: muscle motor protein dysfunction - a side effect of intensive care unit treatment. - Friedrich, Oliver; Diermeier, Stefanie; Larsson, Lars (Acta Physiologica, 2018)
Intensive care interventions involve periods of mechanical ventilation, sedation and complete mechanical silencing of patients. Critical illness myopathy (CIM) is an ICU-acquired myopathy that is associated with limb muscle weakness, muscle atrophy, electrical silencing of muscle and motor proteinopathy. The hallmark of CIM is a preferential muscle myosin loss due to increased catabolic and reduced anabolic activity. The ubiquitin proteasome pathway plays an important role, apart from recently identified novel mechanisms affecting non-lysosomal protein degradation or autophagy. CIM is not reproduced by pure disuse atrophy, denervation atrophy, steroid-induced atrophy or septic myopathy, although combinations of high-dose steroids and denervation can mimic CIM. New animal models of critical illness and ICU treatment (i.e. mechanical ventilation and complete immobilization) provide novel insights regarding the time course of protein synthesis and degradation alterations, and the role of protective chaperone activities in the process of myosin loss. Altered mechano-signalling seems involved in triggering a major part of myosin loss in experimental CIM models, and passive loading of muscle potently ameliorates the CIM phenotype. We provide a systematic overview of similarities and distinct differences in the signalling pathways involved in triggering muscle atrophy in CIM and isolated trigger factors. As preferential myosin loss is mostly determined from biochemistry analyses providing no spatial resolution of myosin loss processes within myofibres, we also provide first results monitoring myosin signal intensities during experimental ICU intervention using multi-photon Second Harmonic Generation microscopy. Our results confirm that myosin loss is an evenly distributed process within myofibres rather than being confined to hot spot
Keywords: second harmonic generation microscopy; skeletal muscle; critical illness; preferential myosin loss; myofibrillar proteins